Clinical study of voiding disorders in patients with cerebrovascular accidents - Murayama, K (Hinyokika kiyo. Acta urologica Japonica, 1991)
Cystometry and urethral pressure profile were determined in 41 patients (29 males and 12 females) with voiding disorders resulting from cerebrovascular accidents within one year after the episode. By clinical symptoms, they were classified into 3 groups, urge incontinence (14 patients, 34%), pollakisuria (10 patients, 24%) and dysuria (17 patients, 41%). Cystometrogram were classified into 3 types, hyperactive bladder (31 patients, 76%), normal bladder (5 patients, 12%) and hypoactive bladder (5 patients, 12%). All patients in both groups of incontinence and pollakisuria showed hyperactive bladder except one normal bladder, while in the group of dysuria 3 types of cystometrograms were observed. Bladder capacity in incontinence group showed tendency to be smaller than that in dysuria group who had hyperactive bladder. Maximum urethral pressure in incontinence group was significantly lower than that in pollakisuria group and dysuria group who had hyperactive bladder. Ten patients with cerebral cortical lesions (80%) showed hyperactive bladder and 60% of them showed incontinence. In patients with cerebral lesions who had hyperactive bladder, the maximum urethral pressure of patients with incontinence showed tendency to be lower than that of patients with pollakisuria and dysuria. The majority of 7 patients with thalamic lesions showed hyperactive bladder and normal urethral pressure, and had dysuria. Two patients with pontine lesions showed hypoactive bladder. These findings suggested that urge incontinence resulting from cerebrovascular accidents was due not only to hyperactive bladder but also to lower urethral pressure